The Role of Fresh Graduates as Learning Volunteers in the Covid-19 Pandemic - Bertholomeus Jawa Bhaga (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aim to knowing the effectiveness of efforts to empower the latest undergraduate graduates to help volunteer for learning during the Covid-19 pandemic. This research is qualitative research with a descriptive method that seeks to describe the role that the undergraduate can become a volunteer for learning. Data analysis techniques are in the form of collecting data from respondents. Data is reduced, data is presented, and then analyzed. The results obtained were found that fresh graduates were graduates who had just graduated from campuses around the Flores area in general and IKIP Muhammadiyah Maumere in particular and their roles in many ways teachers, students and being assistants. Parents in accompanying their children to study at and from home. From the implementation of this volunteer, it was found that there were changes in connection with the assisted learning process from home, which was enforced, school children felt helped in terms of progress in subject matter and were not left behind in understanding the material provided by teachers from school, parents and students also got new knowledge about the use of IT.